IMPACT OF AUDIT QUALITY ON FINANCIAL REPORTING QUALITY OF LISTED OIL AND GAS FIRMS IN NIGERIA: THE MODERATING ROLE OF INTERNAL CONTROL SYSTEM (ICS) - HAUWA , DAVID; MURTALA , ABDULLAHI; DACHOMO, GLORIA PAM (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The increase in a number of scandalous reportage in the last three decade have led to apprehensions about legitimacy of most firms financial reporting qualities. This study investigated the moderating effect of internal control system (ICS) on the relationship between audit quality and financial reporting quality (FRQ) of listed oil and gas firm in Nigeria. For a period of ten years (2013-2022). The study has employed the use of regression model as technique of analysis. The population of the study is all the 13 oil and gas companies listed on the Nigerian stock exchange as at 31st December, 2022 and a purposive sampling techniques was adopted in arriving at the 10 samples. Secondary data was employed and data were extracted from the financial statements of the all samples oil and gas firm in Nigeria. The study findings is that both auditor fee (AF), audit size (AS) and internal control system (ICS) has a significant impact on the FRQ of oil and gas firms in Nigeria while audit tenure (AT), Leverage (LEV)) and firms size (FSIZE) has no significantly impact FRQ of the sampled oil and gas firms in Nigeria. The study also confirmed that ICS only moderated AF, AS and AT the sampled firms. The study therefore, concluded that both AF, AT and AS has significant and positive impact on the FRQ of listed oil and gas firms in Nigeria. The study further concluded that ICS significantly moderated the relationship between AF (ICS_AF),AS (ICS_AS ), AT (ICS_AT ) and FRQ of the listed sampled firms. This study therefore recommended that the composition of internal control system for the oil and gas firms should be sustained and improved upon in order to enhance audit quality since it moderated both AF, AS and AT significantly.